A LiF(200) double‐curved crystal for performance improvement of a monochromatic X‐ray fluorescence source. (22nd February 2021) - Cheng, Dawei; Liu, Mingbo; Ni, Ziyue; Shen, Xuejing; Jia, Yunhai
Abstract : LiF(200) diffraction crystals are commonly used in high‐power wavelength‐dispersive X‐ray fluorescence (XRF) but seldom in benchtop energy‐dispersive XRF instruments because of their low diffraction efficiencies. We herein describe a method of producing a double‐curved crystal (DCC) from an LiF(200) plate crystal, wherein diverging X‐rays onto the DCC can be totally diffracted and focused. This improves the performance of a monochromatic wavelength X‐ray fluorescence (MWXRF) source. The characteristic 5.415 keV line of a chromium target was diffracted by an LiF(200) DCC; this MWXRF was used to detect weak signals of trace light elements with atomic numbers 11–22 because of the extremely low and continuous background spectrum. The MWXRF intensity approached 5.3 × 10 8 cps, and it exhibited excellent focusing with a 0.24 × 0.52 mm focal spot. Trace‐ and high‐concentration levels were calibrated respectively to ensure good accuracy. The lower limits of detection of sulfur and chlorine in oils were 1.75 and 0.63 μg/g, respectively. The MWXRF source could be developed into an integrated device including a mini‐focus X‐ray tube and an LiF(200) DCC. Designing the DCC to diffract characteristic MWXRF would provide a system of practical applicability, especially for some serious overlapping and interferential spectral lines.